Pengaruh E-Service Quality dan E-Trust Terhadap E-Loyalty yang di Mediasi oleh E-Satisfaction Pengguna Access by Kai di Kota Bandung - Azzam Muhammad Rizki; Hariyadi Triwahyu Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This observation aims to to evaluate the quality of E-Service and trust in E-Loyalty and E-Satisfaction as mediating variables for users of the Access By KAI application in Bandung City. The background of this research is based on the high use of the Access By KAI application but accompanied by many negative reviews from users, such as system errors and slow top-up processes. This study uses a quantitative approach with a survey method and a non-probability sampling technique, namely convenience sampling. Data was obtained from 120 respondents who had used the Access By KAI application. Data processing was carried out by multiple regression analysis and the Sobel test to see the effect of mediation. The results of the study show that E-Service Quality and E-Trust have a positive and significant effect on E-Satisfaction, and also affect E-Loyalty. However, E-Satisfaction had no effect as a mediation in this study. These findings indicate that improving service quality and digital trust can increase user satisfaction and loyalty to the application. This research makes a practical contribution to PT KAI in an effort to improve the user experience through strengthening service systems and application security.